Endothelin-1 as a master regulator of whole-body Na+ homeostasis - Speed, Joshua S.; Heimlich, J. Brett; Hyndman, Kelly A.; Fox, Brandon M.; Patel, Vivek; Yanagisawa, Masashi; Pollock, Jennifer S.; Titze, Jens; Pollock, David M. (The FASEB Journal, 2015)
The current study was designed to determine whether vascular endothelial-derived endothelin-1 (ET-1) is important for skin Na(+) buffering. In control mice (C57BL/6J), plasma Na(+) and osmolarity were significantly elevated in animals on high- vs. low-salt (HS and LS, respectively) intake. The increased plasma Na(+) and osmolarity were associated with increased ET-1 mRNA in vascular tissue. There was no detectable difference in skin Na(+):H2O in HS fed mice (0.119 ± 0.005 mM vs. 0.127 ± 0.007 mM; LS vs. HS); however, skin Na(+):H2O was significantly increased by blockade of the endothelin type A receptor with ABT-627 (0.116 ± 0.006 mM vs. 0.137 ± 0.007 mM; LS vs. HS; half-maximal inhibitory concentration, 0.055 nM). ET-1 peptide content in skin tissue was increased in floxed control animals on HS (85.9 ± 0.9 pg/mg vs. 106.4 ± 6.8 pg/mg; P < 0.05), but not in vascular endothelial cell endothelin-1 knockout (VEET KO) mice (76.4 ± 5.7 pg/mg vs. 65.7 ± 7.9 pg/mg; LS vs. HS). VEET KO mice also had a significantly elevated skin Na(+):H2O (0.113 ± 0.007 mM vs. 0.137 ± 0.005 mM; LS vs. HS; P < 0.05). Finally, ET-1 production was elevated in response to increasing extracellular osmolarity in cultured human endothelial cells. These data support the hypothesis that increased extrarenal vascular ET-1 production in response to HS intake is mediated by increased extracellular osmolarity and plays a critical role in regulating skin storage of Na(+).
EVALuna2:3884